Forecasting Share Prices: A Good Practive or a Waste of Time - Bhatt, Mayank V.; Sheth, Nishchit N.; Patel, Tushar N. (Indian Journal of Finance, 2010)
Today, financial markets are extremely volatile by nature and hence, the risk factor is an important concern for all the investors who want to invest their money in the stock market. Is there any measure or criteria to forecast the next day stock price? Does any model exist in the market which can forecast the next day stock price exactly? This study is carried out to generate a general, sector wise forecasting model for all the existing BSE 30 companies and examines their price variation pattern with respect to the BSE Index.